HUBUNGAN LITERASI KESEHATAN DENGAN PERILAKU KONSUMSI SUGAR SWEETENED BEVERAGES DAN FAST FOOD PADA MAHASISWA: RELATIONSHIP BETWEEN HEALTH LITERACY WITH STUDENTS SSBS AND FAST FOOD CONSUMPTION BEHAVIOR - Hanifa Insani Aulia; Tony Arjuna; Bagas Suryo Bintoro (Politeknik Kesehatan Kemenkes RI Jakarta I, 2026)
Health literacy has a statistically significant relationship with education level. In general, university students experience higher psychological stress than non-students, which can have a negative impact on their lifestyle and unhealthy eating patterns, such as sugar-sweetened beverages (SSBs) and fast food. This study was conducted to examine the relationship between health literacy and patterns of SSB and fast food consumption among college students. This study used an observational research design with a cross-sectional approach. The statistical test used is logistic regression. Respondents with good health literacy were 49.3% less likely to consume excessive SSBs than students with low health literacy (OR = 0.507; p<0.001). Similar with fast food consumption behavior, respondents with good health literacy tended to be 7% less likely to consume excessive amounts of fast food (OR = 0.93; p>0.05). This study reveals that good health literacy can reduce the likelihood of students consuming excessive amounts of SSBs and fast food, although not significantly for fast food, through behavioral control and intention.